Efecto de la temperatura de síntesis en el tamaño y ancho de banda prohibida de nanopartículas de Zno producidas por sol-gel - Castillo Jauregui, Luis Angel (2011)
In this work a systematic investigation on the effect synthesis of temperature_x000D_ (from 0 to 40°C) and ageing time on the size and width of the energy band gap of_x000D_ ZnO nanoparticles, which have been synthesized by a modified Sol-Gel method, is_x000D_ reported. The optical properties of ZnO nanoparticles have been evaluated by_x000D_ their UV-vis absorption spectra, from which the size and energy band gap were_x000D_ obtained. The average of nanoparticle size ranged from 2.06nm to 6.78nm as the_x000D_ temperature was increased from 0ºC to 40°C, while the band gap decreases from_x000D_ 3.99eV to 3.46eV, respectively. A distribution of nanoparticle particle size also was_x000D_ observed for all temperatures and ageing times